Sepsis survivors and caregivers perspectives on post–acute rehabilitation and aftercare in the first year after sepsis in Germany - Born, Sebastian; Matthäus-Krämer, Claudia; Bichmann, Anna; Boltz, Hannah-Sophia; Esch, Marlene; Heydt, Luisa; Sell, Stefan; Streich, Kathleen; Scherag, André; Reinhart, Konrad; Hartog, Christiane S.; Fleischmann-Struzek, Carolin (Frontiers in Medicine, 2023)
Background: Sepsis survivors often suffer from new morbidities. Current rehabilitation therapies are not tailored to their specific needs. The perspective of sepsis survivors and their caregivers on rehabilitation and aftercare is insufficiently understood. We aimed to assess how sepsis survivors in Germany rated the suitability, extent and satisfaction with rehabilitation therapies which they underwent in the year following the acute sepsis episode. Methods: Prospective mixed-methods, multicenter study among a cohort of adult ICU-treated sepsis survivors and their caregivers. Interviews were conducted 6 and 12 months after ICU by telephone and comprised closed as well as open-ended questions. Primary outcomes were the utilization and patient satisfaction with inpatient and outpatient rehabilitation and post-sepsis aftercare in general. Open-ended questions were analyzed according to the principles of content analysis. Results: 400 interviews were performed with 287 patients and/or relatives. At 6 months after sepsis, 85.0% of survivors had applied for and 70.0% had undergone rehabilitation. Among these, 97% received physical therapy, but only a minority reported therapies for specific ailments including pain, weaning from mechanical ventilation, cognitive deficits of fatigue. Survivors were moderately satisfied with the suitability, extent, and overall results of received therapies and perceived deficits in the timeliness, accessibility, and specificity of therapies as well as deficits in the structural support frameworks and patient education. Conclusions: From the perspective of survivors who undergo rehabilitation, therapies should already begin in hospital, be more appropriate for their specific ailments and include better patient and caregiver education. The general aftercare and structural support framework should be improved.